DAMPAK AKTIVITAS GALERI INVESTASI BEI TERHADAP MINAT BERINVESTASI (STUDI KASUS PADA MAHASISWA UNIVERSITAS TRIDINANTI PALEMBANG) - Dwi Riana; Royda Royda (Universitas Prof. Dr. Hazairin SH, 2021)
This research aims to find out impact of investment gallery activities against the iterests of student investmest at the Universitas Tridinanti. This type of research is comparative. Sampling techniques is purposive sampling and criteria of students who have income. The population are 4209 students. The samples as many as 250 respondents. Data analysis techniques using wilcoxon test. The primary data sourcers with the techniques of data collection using the interview, questionnaire., and observation. The result showed that there is a difference of interest of student investment before and after the follow the investment gallery activities with siginificance value of 0.000. This proves that the investment gallery activities is quite affective.